Comparing the impact of environmental factors during very high gravity brewing fermentations - Lima, Luís (2011)
The impact of the initial dissolved oxygen, fermentation temperature, wort concentration and yeast pitching rate on the major fermentation process responses were evaluated by full factorial design and statistical analysis by JMP 5.01 (SAS software) software. Fermentation trials were carried out in 2L-EBC tall tubes using an industrial lager brewing yeast strain. The yeast viability, ethanol production, apparent extract and real degree of fermentation were monitored. The results obtained demonstrate that very high gravity worts at 22°P can be fermented in the same period of time as a 15°P wort, by raising the temperature to 18°C, the oxygen level to about 22 ppm, and increasing the pitching rate to 22 × 106 cell/mL. When diluting to obtain an 11.5°P beer extract, the volumetric brewing capacity increased 91% for the 22°P wort fermentation and 30% using the 15°P wort. After dilution, the fermentation of the 22°P wort resulted in a beer with higher esters levels, primarily the compound ethyl acetate.